Egypt's Policy Toward the Palestinian Conflict: a Historical and Contemporary Analysis - Hovhannisyan, Artak H.
This article provides a comprehensive examination of Egypt's policy toward the Palestinian conflict, from its historical role as a mediator and advocate for Palestinian rights to its contemporary approach in the ever-evolving geopolitical landscape of the Middle East. Through a nuanced analysis, this paper delves into the key factors shaping Egypt's policy and its impact on the broader dynamics of the Israeli-Palestinian conflict. Эта научная статья представляет собой всестороннее исследование политики Египта в отношении палестинского конфликта, от его исторической роли посредника и защитника прав палестинцев до его современного подхода в постоянно меняющемся геополитическом ландшафте Ближнего Востока. С помощью тонкого анализа эта статья углубляется в ключевые факторы, формирующие политику Египта, и ее влияние на более широкую динамику израильско-палестинского конфликта.
Keywords: History